Long-Term Moderate-Level Noise Exposure Caused Hyperexcitability in the Central Auditory System - Fei Xu; Guangdi Chen; Li Li; Wei Sun (Neural Plasticity)
Noise exposure is one of the most common causes of hearing loss and hyperacusis. Studies have shown that noise exposure can induce a cortical gain to compensate for reduced input of the cochlea, which may contribute to the increased sound sensitivity. However, many people with hyperacusis have no measurable cochlear lesion after being exposed to loud sound. In this experiment, we studied the neurological alterations in the cortical and subcortical areas following a prolonged moderate level of noise exposure (84 dB SPL, 8 h/day for 4 weeks) in the laboratory mice. The cochlear function was monitored by auditory brainstem responses (ABRs). The behavioral auditory sensitivity and temporal processing were evaluated using the acoustic startle response (ASR) and gap-induced prepulse inhibition (gap-PPI). The central auditory functions were determined by electrophysiological recordings of the inferior colliculus (IC) and the auditory cortex (AC). Our results showed that although there was no significant difference in the ABR thresholds, the noise group showed enhanced ASR and gap-PPI compared to the control group. Increased neural activity in both the IC and the AC was recorded in the noise-exposed mice compared to the control group, suggesting a central gain in both the subcortical and cortical regions. The current source density (CSD) analysis of the AC response revealed an increased columnar excitation and reduced corticocortical projection in the noise group, different from the central gain model of noise-induced hearing loss. Our results suggest that chronic “nondestructive” noise can increase the gain of the central auditory system by altering the balance of auditory thalamocortical and intracortical inputs, which may contribute to the increased sound sensitivity in people with normal hearing.